Analisis dan Modifikasi Desain Grate Cooler Pabrik Semen - Akhyarsi, Odi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
This study analyzes the case of wall layer damage in the bullnose area of a cement plant's grate cooler, proposes alternative design modifications, and evaluates the design alternatives. The case analysis and design evaluations were conducted using Computational Fluid Dynamics (CFD) approach. The results for the actual grate cooler indicate that the air flow temperature around the bullnose surface is very high, approximately 1500K, and the bullnose surface is exposed to air flow with a velocity of 4-5 m/s. The combination of high flow temperature and velocity is suspected to be the cause of erosion on the grate cooler wall surface. Two design alternatives were proposed and considered: Design A, where the right-angle forming the bullnose is eliminated, and Design B, where the bullnose position is shifted back by 13 meters and tertiary air channel are integrated with the kiln hood. Design A was found to reduce the air flow temperature around the bullnose surface by 100K. The best results were obtained with Design B, where the air flow temperature around the bullnose surface could be significantly reduced by approximately 400K, to 1000K. In both designs, the air velocity near the bullnose could be lowered to 2-4 m/s. This study recommends Design B as a solution to prevent recurring damage to the wall layer in the bullnose area of the grate cooler.